2019
DOI: 10.4093/dmj.2018.0080
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum Angiopoietin-Like 6 Ahead of Metabolic Syndrome in a Prospective Cohort Study

Abstract: Background Despite being an anti-obesity hepatokine, the levels of serum angiopoietin-like 6 (ANGPTL6) are elevated in various metabolic diseases. Thus, ANGPTL6 expression may reflect metabolic burden and may have compensatory roles. This study investigated the association between serum ANGPTL6 levels and new-onset metabolic syndrome. Methods In total, 221 participants without metabolic syndrome were randomly selected from a rural cohort in Korea. Baseline serum ANGPTL6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 36 publications
2
11
1
Order By: Relevance
“…Previously, we confirmed in mouse models that serum ANGPTL6 levels were increased by high fat diet and attenuated by exercise training [6]. Based on this, we interpreted our results in a prospective cohort study that upregulation of ANGPTL6 is a protective response alleviating metabolic stress [1]. We suggest that increased serum ANGPTL6 levels in a preclinical status reflect the increase in ongoing metabolic stress; thus, it could be used as a predictable biomarker of development of metabolic syndrome.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…Previously, we confirmed in mouse models that serum ANGPTL6 levels were increased by high fat diet and attenuated by exercise training [6]. Based on this, we interpreted our results in a prospective cohort study that upregulation of ANGPTL6 is a protective response alleviating metabolic stress [1]. We suggest that increased serum ANGPTL6 levels in a preclinical status reflect the increase in ongoing metabolic stress; thus, it could be used as a predictable biomarker of development of metabolic syndrome.…”
supporting
confidence: 68%
“…We really appreciate Dr. Kim for expressing interest and providing valuable comments on our recently published article, “Increased serum angiopoietin-like 6 ahead of metabolic syndrome in a prospective cohort study” which was published in Diabetes & Metabolism Journal [1].…”
mentioning
confidence: 99%
“…Thus, our baseline data are consistent with the evidence from previous clinical studies showing that each of the three biomarkers are markedly elevated in MetS patients [ 17 , 25 , 29 ]. Furthermore, possessing potential as independent predictors of new-onset MetS, these stress markers may be useful in the screening and prediction of individuals at high risk of acquiring metabolic disorders, and in making early intervention decisions during pre-clinical stages [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, ANGPTL6 is regarded as a metabolically beneficial hepatokine since it exerts anti-obesogenic and insulin-sensitizing effects [ 15 ]. However, paradoxically, elevated serum ANGPTL6 concentrations have been found prior to MetS onset (in a prospective cohort study) in addition to being found in MetS patients (a cross-sectional study) [ 17 , 31 ]. Hence, we have suggested that circulating ANGPTL6 levels have a strong predictive potential and diagnostic value for MetS.…”
Section: Discussionmentioning
confidence: 99%
“…In this article entitled “Increased serum angiopoietin-like 6 ahead of metabolic syndrome in a prospective cohort study,” Namkung et al [10] prospectively evaluated the association between serum ANGPTL6 level and new-onset metabolic syndrome in a rural cohort in Korea. They showed that serum ANGPTL6 level was already significantly elevated before developing new-onset metabolic syndrome, which has an independent predictive value for metabolic syndrome.…”
mentioning
confidence: 99%